Contemporary Conflict Resolution and Islamic Conflict Resolution: Similarity and Differentiation on the Theoretical Level - Nabilla Sabban (Universitas Muhammadiyah Yogyakarta, 2014)
The critiques towards Cosmopolitan conflict resolution theory that it cannot be applied universally because it is incompatible with the characteristics of the conflict in the other part of the world beyond Western significantly influence the field. Several scholars argue that the theory - specifically cannot help to solve the current conflicts that generally happen in the Islamic Worlds or Countries or involved Islamic fundamentalist group because it was taken from the culture, the norms and the values of Christian Western Europe and North America experiences. Thus, this rise a question, do we need to have new perspective or theory of Conflict Resolution to solve particular conflicts in the Islamic World or Countries - such as from the Islamic perspective? However, it is not easy since Islam particularly after 9/11 is commonly identified as religion and culture that inherently violent. Stand from this point of view the author want to explore on the essay whether the Cosmopolitan Conflict Resolution seriously cannot be applied universally especially in the Islamic World and pop up with the possibility of Conflict Resolution theory from the Islamic perspective.